UTILIZING MAPS AS A LEARNING MEDIA FOR HISTORY SUBJECT AT SMA PGRI 2SERAM KAIRATU - Gazali Far-Far; Johan Pattiasina; Meliyana Kakerisa (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
It is expected that teachers can manage the use of learning media to support the learning process following the goal of education. The purpose of this study was to see the effectiveness of using maps as a learning media to solve the teachers’ difficulties in presenting the topics/materials in history subject. This research was conducted at SMA PGRI 2 Seram-Kairatu. This study used a qualitative research method with a descriptive approach. The description in this study was focused on describing the learning plan, media types, media selection, and the application of maps as learning media. The data obtained in this study included the results of observations, interviews, and documentation. Based on the research results, firstly, the teacher prepared a Lesson Plan (RPP) and Syllabus. Secondly, the teacher used maps as a medium of learning, especially in history subjects. Thirdly, the use of maps as learning media was following the topics/materials being taught. Thus, the conclusion of this study was that using maps as a learning media provided convenience for history teachers in explaining the material to students. In addition, the use of maps as learning media was adjusted to the material taught by the teacher.